Kulturelle Differenz und Übersetzung in Organisationen. Eine ethnographische Studie in Einrichtungen grenzüberschreitender Jugendarbeit und Weiterbildung - Engel, Nicolas; Göhlich, Michael (Zeitschrift für Pädagogik, 2013)
The authors discuss findings of an ethnographic study carried out in trans-regionally rooted organizations. An investigation of the question of how organizations of youth work and of further education working on a programmatic cross-border level deal with cultural differences resulting from this crossing of borders leads to two different results. The practical production and treatment of differences may, on the one hand, take the form of a process of the reproduction of cultural differences and, on the other hand, that of a process of the hybridization of cultural differences. Following the translational turn, these processes can - from an organizational-pedagogical perspective - be identified as cultural translation processes of the tradition or transformation of organization-specific knowledge and skills of border-crossing.